LIVING LAW AND WOMEN EMPOWERMENT: Weaving Skills as a Marriage Requirement in Sade, West Nusa Tenggara - Sugitanata, Arif; Aminah, Siti; Muhasim, Ahmad (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2022)
Weaving skills as a marriage requirement in the Sade Muslim Society is one of the customary rules—living law—that remains to exist currently, although it is not stated according to Islamic law or state law in the place. Departing from that uniqueness, this study aims to explore the reasons behind that term. Data was collected through interviews and observation in the field. Inspired by Turner’s symbolic anthropological theory, this study shows that the enforcement of customary rules—the prohibition of marriage for girls who do not yet have weaving skills—is interpreted as a form of cultural preservation. It is an effort to strengthen the micro-economy of the society with the hands of Sade women, which later becomes beneficial for their position in the family after marriage. Furthermore, the meaning of this customary rule is to preserve the identity of the Sade society which features the maturity and independence of women before going married.[Ketrampilan menenun sebagai syarat perkawinan di Masyarakat Muslim Sade merupakan salah satu aturan adat yang masih hidup hingga saat ini, meskipun tidak diatur menurut hukum Islam atau hukum negara di tempat tersebut. Berangkat dari keunikan tersebut, penelitian ini bertujuan untuk menggali alasan di balik istilah tersebut. Pengumpulan data lebih banyak melalui wawancara dan observasi di lapangan. Terinspirasi oleh teori antropologi simbolik Turner, penelitian ini menunjukkan bahwa penegakan aturan adat yang melarang pernikahan bagi anak perempuan yang belum memiliki keterampilan menenun dimaknai sebagai bentuk pelestarian budaya. Ini merupakan upaya penguatan ekonomi mikro masyarakat dengan tangan-tangan perempuan Sade, yang nantinya bermanfaat bagi posisi mereka dalam keluarga setelah menikah. Selanjutnya, makna dari aturan adat ini adalah untuk melestarikan identitas masyarakat Sade yang menonjolkan kedewasaan dan kemandirian perempuan sejak sebelum menikah.]